The Devil’s Threat in Medieval Bestiaries: Recognizing and Resisting Evil in the Dragon, Serpent, Wolf, Fox, Ape, Whale, Hawk, Partridge, and Raven - Jane Beal (Ítaca)
To medieval contemplatives, the devil posed a clear spiritual threat to those seeking to be piously devoted to Jesus. To avoid the plotting of the devil, monastics were advised to pray and study the scriptures. This they did, not only by means of biblical manuscripts, but also medieval bestiaries, in which the scriptures were incorporated alongside illustrative images, scientific information, and allegorical interpretation of the beasts of the world. Several beasts and birds were understood to signify aspects of the devil’s arsenal, especially his vices of deception, pride, and sin. These emerge from his nature as a fallen angel of light who is now ugly, wily, and ever hungry: he seeks to swallow men’s souls by entrapping them with earthly things, hypocrisy, and lust while simultaneously destroying their capacity for good judgement. The animals associated with the devil’s threat included the dragon, serpent, ape, whale, wolf, fox, hawk, partridge, and raven. A closer look at the representation and interpretation of these animals in the exemplary Aberdeen Bestiary can give readers a fuller sense of the spiritual struggle that medieval Christian contemplatives felt themselves to be in as well as the wisdom they used to combat and overcome the diabolical threat.